Cerita Rakyat Penamaan Desa di Kerinci: Kategori dan Fungsi Sosial Teks - Irzal Amin; Syahrul R; Ermanto . (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: The aim of this research is to describe text category and social function of the naming village folktale. Data were gathered through two steps. First, the speech acts were recorder using audiovisual recording. After that, the recording was transcribed from regional language to Indonesian language. Second, the data of category and social function of naming village folktale were conducted through note talking, observation and interview. Then, the data were analyzed through four steps, (1) data inventory, (2) classification, (3) discussions and conclusions, and (4) data reporting. The result of this research showed that naming village folktale in Kerinci can be categorized into myths, legend and fairy tale which are full of moral values. Moreover, in social function side, this folktale has five social functions as follows: developing society’s integrity, social control, solidarity strengthening, and communal harmonization. Kata kunci: Cerita rakyat penamaan, kategori, fungsi sosial teks